1978
DOI: 10.1210/endo-102-3-791
|View full text |Cite
|
Sign up to set email alerts
|

Data on the Sites of Stimulatory Feedback Action of Gonadal Steroids Indispensable for Luteinizing Hormone Release in the Rat*

Abstract: The sites of the stimulatory feedback action of gonadal steroids on LH release were investigated in estrogen-primed ovariectomized rats. Either estradiol benzoate (E2) or estrone (E1) injections 72 h after E2 priming induced a significant increase in serum LH 30 h later, whereas injections of progesterone (P) did so 6 h later. Horizontal sections placed above the medial preoptic area prevented the increase after E2 injections but not after E1 and P injections. Retrochiasmatic sections or bilateral lesions plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…SCN lesions often attenuated, but never blocked P-induced gonadotro pin release, and ASR and VPC-L lesions did not alter the positive feedback response to P. Thus, the neural system mediating the positive feedback effect of EB appears to be more widely distributed within the suprachiasmatic region than that involved in the positive feedback effect of P. Dif ferential responsiveness to the positive feedback actions of EB and P have also been reported in rats following lesions in other brain areas. For example, knife cuts at the roof of the preoptic area which sever limbic connections to the hy pothalamus, block the positive feedback effect of EB with out interfering with P-induced gonadotropin release [15]. This diffuse vs. circumscribed anatomical organization of EB-and P-sensitive positive feedback systems revealed by lesion studies is closely paralled by a differential distribu tion of estrogen-and progestin-concentrating neurons in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCN lesions often attenuated, but never blocked P-induced gonadotro pin release, and ASR and VPC-L lesions did not alter the positive feedback response to P. Thus, the neural system mediating the positive feedback effect of EB appears to be more widely distributed within the suprachiasmatic region than that involved in the positive feedback effect of P. Dif ferential responsiveness to the positive feedback actions of EB and P have also been reported in rats following lesions in other brain areas. For example, knife cuts at the roof of the preoptic area which sever limbic connections to the hy pothalamus, block the positive feedback effect of EB with out interfering with P-induced gonadotropin release [15]. This diffuse vs. circumscribed anatomical organization of EB-and P-sensitive positive feedback systems revealed by lesion studies is closely paralled by a differential distribu tion of estrogen-and progestin-concentrating neurons in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Effective lesions have been variously described as involving the su prachiasmatic nuclei (SCN) [1,2,5,7,9,13,27,39], the medial basal suprachiasmatic region [15], the organum vas culosum of the lamina terminalis (OVLT) [26], or the medial preoptic nucleus (MPN), a small periventricular structure lying immediately caudal to the OVLT [36,39,40]. Our re-' This work (publication No.…”
mentioning
confidence: 99%
“…Interestingly, both the BST and 1-SEPT are located within the area indispensable for the stimulatory feedback action of estradiol on LH release in EB-primed ovariectomized rats (Kawakami et al, 1978b). Furthermore, the MPO is a sensitive area to estrone.…”
Section: Endocrinolmentioning
confidence: 97%
“…3, Fig. 4 (Kawakami et al, 1978). It was reported that the perikarya of the LH-RH neurons are mainly located in the POSC.…”
Section: Resultsmentioning
confidence: 89%